2012
DOI: 10.1029/2011jc007655
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of ocean acidification in naturally variable coral reef flat ecosystems

Abstract: [1] Ocean acidification leads to changes in marine carbonate chemistry that are predicted to cause a decline in future coral reef calcification. Several laboratory and mesocosm experiments have described calcification responses of species and communities to increasing CO 2 . The few in situ studies on natural coral reefs that have been carried out to date have shown a direct relationship between aragonite saturation state (W arag ) and net community calcification (G net ). However, these studies have been perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
214
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(242 citation statements)
references
References 90 publications
22
214
6
Order By: Relevance
“…For example, increased light levels cause warmer temperatures, which also directly affect X arag (higher temperature increases X arag by decreasing aragonite solubility). Some studies have found a significant relationship between coral calcification and temperature (e.g., Marshall and Clode 2004;Reynaud et al 2004;Silverman et al 2007), while others have not (e.g., Shaw et al 2012). To some extent, a positive relationship between temperature and calcification rates may be due to the effect of temperature on seawater X arag (Silverman et al 2007;Shaw et al 2012), but this effect is relatively small (0.03 units per 2°C).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, increased light levels cause warmer temperatures, which also directly affect X arag (higher temperature increases X arag by decreasing aragonite solubility). Some studies have found a significant relationship between coral calcification and temperature (e.g., Marshall and Clode 2004;Reynaud et al 2004;Silverman et al 2007), while others have not (e.g., Shaw et al 2012). To some extent, a positive relationship between temperature and calcification rates may be due to the effect of temperature on seawater X arag (Silverman et al 2007;Shaw et al 2012), but this effect is relatively small (0.03 units per 2°C).…”
Section: Introductionmentioning
confidence: 96%
“…On diurnal timescales, the same is true for shallow reef systems. For example, large diurnal fluctuations in X arag , from 1.5 to 6 units, have been observed on Lady Eliot Island (GBR) where reef waters are typically less than 1 m deep (Shaw et al 2012). These types of environments provide natural laboratories to investigate rates of calcification under a broad range of seawater X arag .…”
Section: Introductionmentioning
confidence: 99%
“…4). It is well established that for carbonate ecosystems, calcification decreases TA during the day and carbonate dissolution increases TA at night (2017) 23:75-88 81 (e.g., Shamberger et al 2011;Shaw et al 2012;Albright et al 2013), and hence this oscillation clearly does not represent the in situ diel calcification/dissolution signal generated over the reef flat. These underway data were collected roughly 8-10 km downwind from the forereef during the day and 20 km downwind at night.…”
Section: Spatial Scale Impact Of Reef Inorganic Metabolismmentioning
confidence: 99%
“…Although numerous experimental and field studies show that increasing CO 2 and decreasing aragonite saturation state (X ar ) lead to decreased coral calcification rates and increased dissolution rates of carbonate substrates, the predicted point in time at which an individual reef ecosystem will shift from net accretion to net dissolution varies across studies and ecosystems (Silverman et al 2007;Ohde and van Woesik 1999;Langdon et al 2000Langdon et al , 2003Andersson et al 2009;Shamberger et al 2011;Shaw et al 2012;Andersson et al 2014). While the global distribution of coral reefs is governed by light availability, temperature, nutrients and X ar (Kleypas et al 1999), at the local scale, the conditions that determine coral reef calcification, distribution and community composition are much more complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Field studies have recently shown the mean pH shift for the open ocean projected for 2100 (0.2-0.3 pH units, Cao and Caldeira 2008) is often exceeded on a daily basis in some coral reef environments, especially reef flats (Okinawa: Ohde and van Woesik 1999;Nakamura and Nakamori 2009;Panama: Manzello 2010;Galapagos: Manzello 2010; parts of the Great Barrier Reef: Santos et al 2011;Shaw et al 2012;Silverman et al 2012; central equatorial Pacific: Price et al 2012;Hawaiian Islands: Yates and Halley 2006;Florida Reef Tract: Manzello et al 2012). These findings demonstrate that reefs can and do undergo net growth and maintain health in the presence of large diel pH variability up to 0.5-0.6 units.…”
mentioning
confidence: 99%